Age-moderating effects and training characteristics of neuromuscular training for preventing knee injuries: a systematic review and meta-analysis - Youwei Yao; Ming Pan; Xuesong Niu (Frontiers in Public Health, 2026)
Objective Sports-related knee injuries are common and may cause pain, joint damage, reduced sport participation, and long-term physical activity limitations. Although neuromuscular training (NMT) is widely used for injury prevention, whether its effectiveness is moderated by age or intervention characteristics remains unclear. This systematic review and meta-analysis evaluated the effectiveness of NMT for preventing sports-related knee injuries and examined the influence of age and training characteristics. Methods PubMed, Embase, Web of Science, The Cochrane Library, and EBSCO (SPORTDiscus) were searched from inception to September 30, 2025. Thirty studies were included following PRISMA guidelines. Random-effects meta-analysis, subgroup analyses, meta-regression, heterogeneity assessment, and risk-of-bias assessment using RoB 2 and ROBINS-I were performed. Results Thirty studies were included. NMT significantly reduced knee injury risk in athletes (effect estimate = 0.670, 95% CI: 0.547–0.820, p < 0.001), with moderate heterogeneity ( I 2 = 58.5%). Age subgroup analyses showed protective effects in athletes aged >18 years (effect estimate = 0.566) and ≤18 years (effect estimate = 0.718), with no significant between-subgroup difference. Meta-regression did not identify study-level moderation by mean age or female proportion. Interventions incorporating landing-stabilization, plyometric, core, agility, or lower-limb strength training showed significant preventive effects, although between-subgroup differences for individual components were not significant. Multicomponent programs (≥3 components) were associated with significant risk reduction (effect estimate = 0.643), whereas programs with <3 components were not; the between-subgroup difference was significant ( p = 0.045). Standardized programs significantly reduced injury risk (effect estimate = 0.592), whereas non-standardized programs did not. Dose-related analyses suggested that 15–20 min/session, 2–3 sessions/week, and durations >25 weeks may represent relatively stable and clinically interpretable patterns, although dose-related between-subgroup differences were not significant. Conclusion NMT significantly reduces knee injury risk in athletes, with no clear evidence of age-related moderation. Structured, multicomponent, and standardized programs may have practical advantages, but findings on program structure, components, standardization, and dose should be interpreted cautiously because these analyses were exploratory. Systematic review registration PROSPERO, under registration number CRD420261327352.